Calcium Carbonate Production, Coral Cover and Diversity along a Distance Gradient from Stone Town: A Case Study from Zanzibar, Tanzania - Herrán, Natalia; Narayan, Gita R.; Reymond, Claire E.; Westphal, Hildegard (Frontiers in Marine Science, 2017)
Photosymbiotic scleractinian corals are major bioengineers in tropical coastal waters, where they build structurally complex geological features and provide substrata for a manifold of macro and microhabitats. On a local scale, ecological competition and physical parameters - natural as well as human-derived, alter species richness, biodiversity, and morphological adaptation on tropical coral reefs. Here, we compared four coral reefs in the Zanzibar Archipelago at different distances from Stone Town and under different management regimes. To assess the ecological health of these reefs, calcium carbonate production, structural complexity, and α-diversity were determined. The unprotected reefs in the direct vicinity of Stone Town, which are exposed to fishing pressure, land-derived pollution, unregulated tourism, and careless anchoring, showed the lowest calcium carbonate production (8.47 ± 4.37 kg CaCO3 m-2 yr-1), coral cover (52.4 ± 13.9%), and diversity (H´=0.94 ± 0.37). Conversely, the furthest reef and marine protected area showed the highest net calcium carbonate production (16.90 ± 9.70 kg CaCO3 m-2 yr-1), coral cover (67.4 ± 8.7%), and diversity (H´=1.74 ± 0.20). In comparison to other bioregions and/or reefs of the Indian Ocean, estimates of calcium carbonate production and coral cover (>50%) were relatively high. Moreover, coral community structure differs significantly with distance from Stone Town, in that, the most homogenous reefs dominated by massive and submassive species (Porites lobata and P. rus) occurred the closest to Stone Town.